Diary of Midshipman N K Calder. - Calder, N.K.; Calder, Michael ([Australia] : Midshipman N K Calder, 1917)
"Midshipman N K Calder RAN was one of the original entry of twenty eight Cadet Midshipmen who joined the Royal Australian Naval College at the time of it's foundation on 01 January 1913. After four years study he graduated along with twenty two others who completed their training on 12 December 1916. N K Calder would go on to serve in the RAN for a further 43 years. His specialisation was "Torpedo" and during WW II would command Australia's only minelayer, HMAS Bungaree. He was appointed an Officer of the Order of the British Empire (OBE) on 01 January 1943. On 17 January 1917, Midshipman Calder and the others of his term embarked aboard HMT Omrah and sailed for England and "a great adventure". This copy of the transcript of his father's Diaries for the years 1917 and 1918 has been provided by Mike Calder. For the majority of the two years Midshipman Calder served onboard a capital ship, HMS Royal Sovereign, at Scapa Flow."
Title from title screen (viewed on 17 September 2014)
Mode of access: Available online. Address as at 17/09/14
Selected for archiving
Keywords: Calder, N.K. -- Diaries; World War, 1914-1918 -- Naval operations; World War, 1914-1918 -- Personal narratives, Australian; Australian